Family,Kinship and Marriage in India - Uberoi,Patricia.ed (Oxford;, 2006)
Oxford in India Readings in Sociology and Social Anthropology have been carefully planned to suit the needs of the general reader, students, teachers, as well as scholars from other disciplines. Problems have been posed in general theoretical terms, but Indian ethnography has been used as far as possible to illustrate them. Each volume is devoted to a core area in sociology and social anthropology and brings within one cover important writings, some of which are very difficult to find. In this way it serves the useful purpose of short-circuiting the vast body of writing in a discipline, and at the same time presenting the current state of the art in it. Family, Kinship and Marriage in India attempts to capture the great variety of family types and kinship practices that are to be found in the South Asia region, and the several theoretical formulations which posit an underlying unity in this variety. The readings have been organized into four sections: Regional Varieties, North and South: Descent Groups and the Kindred; Marriage, Alliance and Affinal Transactions; Family, Household, and Social Change. Some sophisticated new analyses of family and kinship have not made a general impact as yet. These have been presented in as accessible a form as possible in this volume. The readings also try to integrate a concern for gender issues into the study of Indian family and kinship. They offer the best of recent work as well as some celebrated classical writings. The volume editor has a long introduction followed by long section introductions explaining the rationale behind her selctions in each section. She also intervences to explain the text when she feels it to be necessary in the form of editorial notes. Each section introduction ends with an annotated bibliography of additional readings and there is an exhaustive bibliography at the end of the book. This volume includes an extremely useful glossary of technical terms in Kinship studies. Patricia Uberoi teaches sociology at Jawaharlal Nehru University, New Delhi and is one of the editors of Contributions to Indian Sociology, Delhi.